Neoconstitucionalismo y argumentación jurídica - García Figueroa, Alfonso (2017)
This paper aims to explore the functions of the theory of legal argumentation (TLA) on Constitutional States and will especially focus on the political and self-reflective functions of the TLA within the framework of a neo-constitutionalistic legal theory. The first part of the paper includes a definition of the TAL and an analysis of its main functions. At the end of the paper the author provides the bases for the development of a neoconstitutionalistic legal theory.